2020
DOI: 10.3390/ijms21228574
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Petri Net-Based Model of the Involvement of Interleukin 18 in Atherosclerosis

Abstract: Interleukin 18 (IL-18) is a proinflammatory and proatherogenic cytokine with pleiotropic properties, which is involved in T and NK cell maturation and the synthesis of other inflammatory cytokines and cell adhesion molecules. It plays a significant role in orchestrating the cytokine cascade, accelerates atherosclerosis and influences plaque vulnerability. To investigate the influence of IL-18 cytokine on atherosclerosis development, a stochastic Petri net model was built and then analyzed. First, MCT-sets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Our previous results [34] confirmed that IL-18 and IFN-γ play a key role in atherosclerosis. In addition, we showed that the impact of renal failure significantly accelerates this pathology.…”
Section: Inflammation-il-18supporting
confidence: 82%
“…Our previous results [34] confirmed that IL-18 and IFN-γ play a key role in atherosclerosis. In addition, we showed that the impact of renal failure significantly accelerates this pathology.…”
Section: Inflammation-il-18supporting
confidence: 82%
“…IL-18 and its dependent pathway (the IL-18-MyD88 axis) also has a crucial role in atherosclerosis. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Our previous study illuminated the association between augmented abdominal adiposity in PCOS women and a state of low-grade inflammation characterized by elevated IL-18 levels [7]. This proinflammatory cytokine, known for its involvement in various metabolic disorders, has been implicated in the pathogenesis of insulin resistance, dyslipidemia, and cardiovascular risk [8,9]. Recent years have witnessed explorations into the roles of novel biomarkers, including meteorin-like protein (Metrnl), also known as subfatin, and zonulin, in PCOS development, progression, and interconnected metabolic disturbances.…”
Section: Introductionmentioning
confidence: 93%